HybridEval: An Improved Novel Hybrid Metric for Evaluation of Text Summarization - Raheem Sarwar; Bilal Ahmad; Pin Shen Teh; Suppawong Tuarob; Tipajin Thaipisutikul; Farooq Zaman; Naif R. Aljohani; Jia Zhu; Saeed-Ul Hassan; Raheel Nawaz; Ali R Ansari; Muhammad A B Fayyaz (Journal of Informatics and Web Engineering)
The present work re-evaluates the evaluation method for text summarization tasks. Two state-of-the-art assessment measures e.g., Recall-Oriented Understudy for Gisting Evaluation (ROUGE) and Bilingual Evaluation Understudy (BLEU) are discussed along with their limitations before presenting a novel evaluation metric. The evaluation scores are significantly different because of the length and vocabulary of the sentences, this suggests that the primary restriction is its inability to preserve the semantics and meaning of the sentences and consistent weight distribution over the whole sentence. To address this, the present work organizes the phrases into six different groups and to evaluate “text summarization” problems, a new hybrid approach (HybridEval) is proposed. Our approach uses a weighted sum of cosine scores from InferSent’s SentEval algorithms combined with original scores, achieving high accuracy. HybridEval outperforms existing state-of-the-art models by 10-15% in evaluation scores.